2017
DOI: 10.1038/srep44424
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in arsenic-induced oxidative lesion via arsenic biomethylation between C57BL/6J and 129X1/SvJ mice

Abstract: Arsenic is a common environmental and occupational toxicant with dramatic species differences in its susceptibility and metabolism. Mouse strain variability may provide a better understanding of the arsenic pathological profile but is largely unknown. Here we investigated oxidative lesion induced by acute arsenic exposure in the two frequently used mouse strains C57BL/6J and 129X1/SvJ in classical gene targeting technique. A dose of 5 mg/kg body weight arsenic led to a significant alteration of blood glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Human genome-wide association studies for mutations promoting arsenic susceptibility identified an AS3MT haplotype that leads to reduced expression of AS3MT and increased toxicity ( Das et al, 2016 ). Recently it was shown that C57BL/6J mice are more susceptible to arsenic-induced oxidative liver injury than 129X1/SvJ mice, and that this difference is related to their reduced capacity for arsenic methylation ( Wu et al, 2017 ). In addition, one study found that alcohol use may decrease methylation of iAs ( Hopenhayn-Rich et al, 1996 ; Tseng, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human genome-wide association studies for mutations promoting arsenic susceptibility identified an AS3MT haplotype that leads to reduced expression of AS3MT and increased toxicity ( Das et al, 2016 ). Recently it was shown that C57BL/6J mice are more susceptible to arsenic-induced oxidative liver injury than 129X1/SvJ mice, and that this difference is related to their reduced capacity for arsenic methylation ( Wu et al, 2017 ). In addition, one study found that alcohol use may decrease methylation of iAs ( Hopenhayn-Rich et al, 1996 ; Tseng, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…D) is consistent with decreased Shp expression in cholestatic C57BL/6 mice induced by BDL but inconsistent with increased Shp expression in 129x1/SvJ mice fed CA‐chow for 1 week . The 129x1/SvJ mice have a profound defect in response to inflammatory stimulus, and C57BL/6 mice are more susceptible to liver damage than 129x1/SvJ mice, so the differences in hepatic responses to BA‐induced toxicity, including Shp expression, are likely a strain‐specific effect.…”
Section: Resultsmentioning
confidence: 72%
“…Although the function of KLHDC4 remains largely elusive, our results revealed that decreased Klhdc4 expression triggers the Atf4 pathway, leading to dysregulation of genes in both apoptosis and adaptive responses to stress. In fact, relative to 129S1/SvJ, C57BL/6J mice were reported to be more susceptible to oxidative hepatic injury after acute arsenic exposure 71 , indicating different stress responses among mouse strains. It is worth noting that increased translation of Atf4 mRNA is stimulated by phosphorylation of several eIF2 kinases in response to different cellular stresses.…”
Section: Discussionmentioning
confidence: 99%